Elucidating the distribution and characteristics of microplastics in water column of the northwestern South China Sea with a large-volume in situ filtration technology (plankton pump) - Li, Changjun; Zhu, Lixin; Wang, Xiaohui; Li, Daoji (Frontiers in Marine Science, 2025)
Microplastic pollution has emerged as an undeniable marine environmental issue. While a distribution map of microplastics in the upper ocean has been established, the patterns of microplastics within the water column remain unclear. In this study, a large-volume in situ filtration device with filtration efficiency of 30 m3/h was employed to investigate microplastics in the deep waters of the South China Sea. The abundance of microplastics ranged from 0.2 to 1.5 items per cubic meter (n/m3), with an average of 0.56 ± 0.40 n/m3. Microplastics are primarily fragments (72.58%) and fibers (20.97%), with the predominant polymer types being polypropylene (PP) and polyethylene terephthalate (PET). The average size of microplastics is 0.91 ± 0.97 mm, with no statistically significant differences observed across different water layers from 50 to 1000 meter (m). Non-metric Multidimensional Scaling (NMDS) analysis indicated that microplastics in the water column primarily originated from surface waters in the studied region. The occurrence of microplastics in the marine water column is a complex environmental process, influenced by a range of oceanographic mechanisms, including biological, chemical, and physical interactions. Our results provided reliable baseline data on microplastics in the water column of the South China Sea, contributing a better understanding to the vertical transport and fate of microplastics in this region.